2019
DOI: 10.3389/fgene.2018.00718
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Heterogeneity

Abstract: Cell-to-cell heterogeneity drives a range of (patho)physiologically important phenomena, such as cell fate and chemotherapeutic resistance. The role of metabolism, and particularly of mitochondria, is increasingly being recognized as an important explanatory factor in cell-to-cell heterogeneity. Most eukaryotic cells possess a population of mitochondria, in the sense that mitochondrial DNA (mtDNA) is held in multiple copies per cell, where the sequence of each molecule can vary. Hence, intra-cellular mitochond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 226 publications
(350 reference statements)
1
106
0
Order By: Relevance
“…Accordingly, Ferree et al (2013) showed that knockout of mitophagy factors led to an accumulation of partly dysfunctional, aged mitochondria. Hence, mitochondria within single mammalian cells are frequently not uniform in function (Aryaman et al, 2018), and hence will be under differential selective constraints between cell types, tissues, and cells in the same tissue. Taken together, functional differences in mitochondrial activities are observed not only at the organism level, but also between and within cells.…”
Section: Selection Acts On the Phenotype-the Various Levels Of Mitochmentioning
confidence: 99%
“…Accordingly, Ferree et al (2013) showed that knockout of mitophagy factors led to an accumulation of partly dysfunctional, aged mitochondria. Hence, mitochondria within single mammalian cells are frequently not uniform in function (Aryaman et al, 2018), and hence will be under differential selective constraints between cell types, tissues, and cells in the same tissue. Taken together, functional differences in mitochondrial activities are observed not only at the organism level, but also between and within cells.…”
Section: Selection Acts On the Phenotype-the Various Levels Of Mitochmentioning
confidence: 99%
“…Overall, our simple model consists of 4 species ðW S ; W F ; M S ; M F Þ, 6 independent parameters, and 15 reactions, and captures the central property that mitochondria fragment before degradation (Twig et al 2008). Throughout this work, we define heteroplasmy as the mutant-allele fraction per cell of a mitochondrially encoded variant (Wonnapinij et al 2008;Samuels et al 2010;Aryaman et al 2019):…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria exist within a network which dynamically fuses and fragments. Although the function of mitochondrial networks remains an open question (Hoitzing et al 2015), it is often thought that a combination of network dynamics and mitochondrial autophagy (termed mitophagy) act in concert to perform quality control on the mitochondrial population (Twig et al 2008;Aryaman et al 2019;Johnston 2019). Observations of pervasive intramitochondrial mtDNA mutation (Morris et al 2017) and universal heteroplasmy in humans (Payne et al 2012) suggest that the power of this quality control may be limited.…”
mentioning
confidence: 99%
“…Overall, our simple model consists of 4 species (W S , W F , M S , M F ), 6 independent parameters and 15 reactions, and captures the central property that mitochondria fragment before degradation (Twig et al, 2008). Throughout this work, we define heteroplasmy as the mutant allele fraction per cell of a mitochondriallyencoded variant (Aryaman et al, 2019;Samuels et al, 2010;Wonnapinij et al, 2008):…”
Section: Stochastic Modelling Of the Coupling Between Genetic And Netmentioning
confidence: 99%
“…Mitochondria exist within a network which dynamically fuses and fragments. Although the function of mitochondrial networks remains an open question (Hoitzing et al, 2015), it is often thought that a combination of network dynamics and mitochondrial autophagy (termed mitophagy) act in concert to perform quality control on the mitochondrial population (Aryaman et al, 2019;Johnston, 2018;Twig et al, 2008). Observations of pervasive intra-mitochondrial mtDNA mutation (Morris et al, 2017) and universal heteroplasmy in humans (Payne et al, 2012) suggest that the power of this quality control may be limited.…”
Section: Introductionmentioning
confidence: 99%